2016
DOI: 10.2134/jeq2014.10.0414
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater Bioretention Systems: Testing the Phosphorus Saturation Index and Compost Feedstocks as Predictive Tools for System Performance

Abstract: A replicated column trial was conducted to evaluate the potential for the phosphorus saturation index (PSI) to predict P movement in bioretention soil mixtures (BSMs). The impact of compost feedstock on BSM performance was also evaluated. Three composts (biosolids/yard, yard/food waste, and manure/sawdust) were each brought to PSI values of 0.1, 0.5, and 1.0 through the addition of Fe-based water treatment residuals (WTRs) to lower the PSI and P salts to increase the PSI. A synthetic stormwater solution was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 42 publications
4
21
1
Order By: Relevance
“…In their study, Brown et al (2016b) propose that the P saturation index (PSI) could be used as a tool to evaluate whether the soil mixes used in GI systems could become a sink or source of nutrients, like N and P, and also of metals, like Zn and Cu. The PSI was developed as a predictive tool to determine the potential of P leaching from soils amended with organic residuals like manures and biosolids (Elliott et al, 2002; Agyin‐Birikorang and O'Connor, 2007) and is based on a strong correlation between the ratio of total P to Fe and Al oxides as determined by oxalate extraction (PSI = P ox /(Fe ox + Al ox ) and the P found in leachate.…”
Section: Benefits Of Urban Green Spacesmentioning
confidence: 99%
See 3 more Smart Citations
“…In their study, Brown et al (2016b) propose that the P saturation index (PSI) could be used as a tool to evaluate whether the soil mixes used in GI systems could become a sink or source of nutrients, like N and P, and also of metals, like Zn and Cu. The PSI was developed as a predictive tool to determine the potential of P leaching from soils amended with organic residuals like manures and biosolids (Elliott et al, 2002; Agyin‐Birikorang and O'Connor, 2007) and is based on a strong correlation between the ratio of total P to Fe and Al oxides as determined by oxalate extraction (PSI = P ox /(Fe ox + Al ox ) and the P found in leachate.…”
Section: Benefits Of Urban Green Spacesmentioning
confidence: 99%
“…The PSI was developed as a predictive tool to determine the potential of P leaching from soils amended with organic residuals like manures and biosolids (Elliott et al, 2002; Agyin‐Birikorang and O'Connor, 2007) and is based on a strong correlation between the ratio of total P to Fe and Al oxides as determined by oxalate extraction (PSI = P ox /(Fe ox + Al ox ) and the P found in leachate. Brown et al (2016b) evaluated three different composts adjusted with Fe‐based drinking water treatment residuals and P salts to PSI values of 0.1, 0.5, and 1.0 on nutrient and metal leaching using a synthetic stormwater solution and also evaluated plant performance. Results indicate that compost from manure/sawdust performed poorly in terms of plant performance.…”
Section: Benefits Of Urban Green Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…For Cu, the compost-amended media was a source during the first three to five storms, but then the media became a sink. Additionally,Brown et al (2016) indicated that the phosphorus saturation index (PSI) could be used as a predictive tool for estimating treatment capacity and that compost source was not a good indicator of the ability of the compost to filter contaminants Logsdon and Sauer (2016b). demonstrated leaching from compost-amended media and recommended that only small amounts of low-nutrient compost should be incorporated into bioretention media.…”
mentioning
confidence: 99%